DIAGENETIC HISTORY OF CARBONATES IN EAST SABAH - RAYMOND, ROZEN REVILENE (Universiti Teknologi PETRONAS, 2015)
During Oligocene – Miocene, there is a major tectonic deformation which cause a widespread of uplift followed by carbonate sedimentation (Gomantong Limestone Formation) when the depositional environment changed from deep to shallow marine. These onshore Gomantong Limestone formations are often isolated and only been exposed due to plantation development and quarrying activities, which lacks in detailed study done onto the carbonate in that area, particularly the diagenetic features. Therefore, this study will focus on the diagenesis of Gomantong Limestone Formation through comprehensive petrography analysis for evaluation of the fossils, mineral structures, microfacies, cement stratigraphy and diagenetic features which is then followed by scanning electron microscopy (SEM) analysis and X-Ray Diffraction (XRD) analysis. The findings show that microfacies of Gomantong Limestone formations range from wackestone to boundstone, which is dominated by benthic foraminifera (Lepidocyclina sp. and Miogypsisna sp.) that deposited in open shelf to shallow marine environment. Gomantong Limestone formations had mostly undergone micritization, cementations and mechanical fracturing in shallow marine to shallow burial diagenetic environment. However, intense cementation occurred during the diagenesis of Gomantong Limestone results in poor potential of reservoir quality.